Pemberdayaan UMKM Melalui Pendampingan Manajemen Bisnis Dan Digital Marketing Di Masa Pandemi Covid-19 - PRATIWI, LUH PUTU KIRANA (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Sales effectiveness is one of the important activities in business as the main source of income. Implementation of business management in the fields of production, finance, and marketing as the basis for increasing the effectiveness of product sales volume. Digital marketing through social media is the main promotion target for Small Micro and Medium Enterprises because it is able to reach a broad market at the lowest cost, especially during the Covid-19 pandemic. The use of digital marketing needs to consider the mode of transmission, time, context, format and reception. This service program is carried out to help Small Micro and Medium Enterprises “Nasi Babi Guling Buk Eka” in Tua Village, Marga Tabanan to implement business management and digital marketing through social media as the main promotional media in an effort to increase sales volume during the Covid-19 pandemic. The methods used in community service activities are counseling, training, and mentoring. The results of the activity show that empowerment activities are able to increase the knowledge and skills of Small, Micro and Medium Enterprises in implementing business management and digital marketing. It is recommended that all Small, Micro and Medium Enterprises continuously implement business management and digital marketing as an effort to increase sales effectiveness during the Covid-19 pandemic. Keywords: Business Management, Digital Marketing, Sales Effectiveness